“We are pests, we have no future”: The prediction of anxiety by perceived discrimination in patients with coronavirus: Mediating role of psychological resilience - Li, Shuhan; Gu, Jiayu (Frontiers in Psychology, 2022)
In a short amount of time, the COVID-19 pandemic has played havoc on social security, and people infected with coronavirus may have suffered from both physical and mental health issues requiring treatment. The purpose of our study was to examine the effect of perceived discrimination on anxiety in patients with coronavirus and to observe the role of psychological resilience as a mediator in this process. 376 patients with coronavirus were given a questionnaire, and 26 of them participated in in-depth interviews. Our results demonstrated that perceived discrimination in patients with coronavirus was predictive of anxiety and that strong perceptions of discrimination reduced patients' psychological resilience levels, thereby triggering severe anxiety. Furthermore, psychological resilience was demonstrated to be a significant predictor of anxiety severity. Psychological resilience has been shown to act as a mediator between perceived discrimination and anxiety. As a response to COVID-19, the government, the media, and the general public should treat patients with coronavirus scientifically and rationally, minimize the secondary psychological damage caused by the perception of discrimination to the special groups of society represented by patients with coronavirus during the pandemic, correct the erroneous stigma generated by the traditional communication process, and prevent the spread of the psychosocial virus.